INHERITANCE DISTRIBUTION BETWEEN SONS AND DAUGHTERS: A COMPARATIVE STUDY OF INDONESIA AND TUNISIA - Ismail Mutawalli (Law Faculty of Universitas Bandar Lampung, 2025)
The distribution of inheritance between male and female children is a complex issue in Islamic family law, considering the varying interpretations and applications of the law in different countries. In Indonesia, the Compilation of Islamic Law (KHI) serves as a reference for inheritance distribution, which is often considered more conservative and tends to allocate a larger share to male children. Meanwhile, Tunisia is known for its progressive approach through the Code of Personal Status (CPS), which has undergone various reforms to enhance gender equality. This study aims to examine how equal inheritance distribution between male and female children is perceived in Islamic family law, and to compare the Islamic family laws of Indonesia and Tunisia regarding the inheritance shares of males and females. Using a qualitative research design, descriptive analysis techniques, and inductive methods are the primary techniques used to trace data and facts to analyze and find answers to the formulated research questions. The results show that in Islamic family law, the distribution of inheritance between males and females is clearly stipulated in the Qur'an, where males receive twice the share of females (Surah An-Nisa verse 11). This is based on the financial responsibilities of males within the family. Therefore, equal inheritance distribution is not in accordance with Sharia. In Tunisia, the laws that establish equal inheritance distribution between males and females are based on principles of justice and gender equality as part of the modernization of family law. In Indonesia, inheritance law is governed by the Compilation of Islamic Law (KHI), which adheres to Sharia principles, while Tunisia has adopted reforms that reflect gender equality. Despite differences in formal legal approaches, both countries uphold the fundamental values of Islam in the distribution of inheritance.